2010
DOI: 10.3354/meps08775
|View full text |Cite
|
Sign up to set email alerts
|

Upwelling areas do not guarantee refuge for coral reefs in a warming ocean

Abstract: Global warming is a severe threat to coral reefs. It has been proposed that upwelling could minimise the thermal stress caused by ocean warming, and therefore upwelling areas may serve as a refuge for corals. Here, using 21 yr of satellite sea surface temperature data, we analysed the degree to which the thermal stress experienced by corals is reduced in 4 seasonal upwelling areas with reef development: Colombia in the southern Caribbean, Panama in the eastern tropical Pacific, Oman in the Arabian Sea and Mada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
61
1
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(69 citation statements)
references
References 56 publications
4
61
1
3
Order By: Relevance
“…These negative effects, however, may be mitigated depending on the intra-annual timing of seasonal upwelling (Chollett et al, 2010), or if upwelling waters derive from rather shallow sources (Riegl and Piller, 2003). In agreement with our inferences regarding calcification in a context of upwelling (endmember 2), a study on z coral calcification in the Galapagos upwelling zone found a negative effect on density but not so on extension rates and calcification rates which were higher than expected from known relationships (Manzello et al, 2014).…”
Section: Upwelling As a Driver Of High Skeletal Productivity?supporting
confidence: 87%
“…These negative effects, however, may be mitigated depending on the intra-annual timing of seasonal upwelling (Chollett et al, 2010), or if upwelling waters derive from rather shallow sources (Riegl and Piller, 2003). In agreement with our inferences regarding calcification in a context of upwelling (endmember 2), a study on z coral calcification in the Galapagos upwelling zone found a negative effect on density but not so on extension rates and calcification rates which were higher than expected from known relationships (Manzello et al, 2014).…”
Section: Upwelling As a Driver Of High Skeletal Productivity?supporting
confidence: 87%
“…Many reefs, not just Ningaloo, are influenced by upwelling that can lower temperatures and elevate nutrient concentrations (Andrews and Gentien 1982;Gove et al 2006;Chollett et al 2010). Fore-reef NO x concentrations at Ningaloo varied substantially between the austral spring and autumn, likely in response to the spring and summer equator-ward wind regime and sporadic upwelling (Hanson et al 2005;Wyatt et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Such waters have been proposed as potential localized coral refugia under times of thermal stress (Riegl and Piller, 2003); however, the cool water is also high in CO 2 and low in arag ; consequently, upwelling environments have the potential to be ocean acidification hot-spots (Feely et al, 2008;Manzello, 2010). Upwelling sites clearly comprise a complex mix of abiotic stressors, with any refuge potentially limited by upwelling time (Chollett et al, 2010). In regions such as the Eastern Tropical Pacific (ETP) and Arabian Sea, marginal coral reef formation has been attributed to the cool upwelled waters creating a "pseudo-high-latitude effect" (Sheppard and Salm, 1988) by reducing reef-building processes (Benzoni et al, 2003).…”
Section: Upwelling Environmentsmentioning
confidence: 99%
“…Upwelling sites, for example, can only offset thermal stress if the pulse of cool upwelled water coincides with a stress-event, yet this is frequently not the case (Chollett et al, 2010). Similarly, seagrass environments can only positively enhance local seawater pH and arag during the day, with the opposite occurring at night due to the dominance of respiration in the absence of photosynthesis (Schmalz and Swanson, 1969).…”
Section: The Potential Of Refuge Environmentsmentioning
confidence: 99%